High-sugar, high-fat, and high-protein diets promote antibiotic resistance gene spreading in the mouse intestinal microbiota. (31st December 2022) - Tan, Rong; Jin, Min; Shao, Yifan; Yin, Jing; Li, Haibei; Chen, Tianjiao; Shi, Danyang; Zhou, Shuqing; Li, Junwen; Yang, Dong
ABSTRACT: Diet can not only provide nutrition for intestinal microbiota, it can also remodel them. However, is unclear whether and how diet affects the spread of antibiotic resistance genes (ARGs) in the intestinal microbiota. Therefore, we employed selected high-sugar, high-fat, high-protein, and normal diets to explore the effect. The results showed that high-sugar, high-fat, and high-protein diets promoted the amplification and transfer of exogenous ARGs among intestinal microbiota, and up-regulated the expression of trfAp and trbBp while significantly altered the intestinal microbiota and its metabolites. Inflammation-related products were strongly correlated with the spread of ARGs, suggesting the intestinal microenvironment after diet remodeling might be conducive to the spreading of ARGs. This may be attributed to changes in bacterial membrane permeability, the SOS response, and bacterial composition and diversity caused by diet-induced inflammation. In addition, acceptor bacteria (zygotes) screened by flow cytometry were mostly Proteobacteria, Firmicutes and Actinobacteria, and most were derived from dominant intestinal bacteria remodeled by diet, indicating that the transfer of ARGs was closely linked to diet, and had some selectivity. Metagenomic results showed that the gut resistance genome could be affected not only by diet, but by exogenous antibiotic resistant bacteria (ARB). Many ARG markers coincided with bacterial markers in diet groups. Therefore, dominant bacteria in different diets are important hosts of ARGs in specific dietary environments, but the many pathogenic bacteria present may cause serious harm to human health.